PEMANFAATAN MEDIA TIK TUTORIAL SEBAGAI KOMPLEMEN EKSPERIMEN PADA PEMBELAJARAN ALAT UKUR SMP - Dian Purnomo; Eko Suyanto; Viyanti Viyanti (Jurnal Pembelajaran Fisika, 2014)
The aims of this research are to understand the increasing of cognitive learning outcomes of students, to build the science process skills of students, to form the character of students, to improve the activities of students and to build the positive attitudes of students that use tutorial ICT media as the experimental complement in measuriment learning.The research has been done in the first semester of academic year 2013/2014 in SMP negeri 1 Seputih Surabaya, Central Lampung. The population of the research was the students of the VII class and the sample of the research was VII C. This research used random sampling technique to choose the sample . The result was able to increase the cognitive learning outcome of students, built the science process skills of students, form the character of students, improve the activities of students and to built the positive attitudes of students.Penelitian ini bertujuan untuk: mengetahui peningkatan hasil belajar ranah kognitif, menumbuhkan KPS, membentuk karakter, mengembangkan aktivitas, dan menumbuhkan sikap siswa terhadap pemanfaatan media TIK tutorial sebagai komplemen eksperimen pada pembelajaran alat ukur. Penelitian berlangsung pada semester ganjil tahun ajaran 2013/2014 di SMP Negeri 1 Seputih Surabaya Kabupaten Lampung Tengah. Sampel yang diambil yaitu kelas VIIC. Pemilihan kelas secara random. Hasil penelitian yaitu terdapat peningkatan hasil belajar ranah kognitif siswa, dapat menumbuhkan KPS siswa, dapat membentuk karakter siswa, dapat mengembangkan aktivitas siswa, dan dapat menumbuhkan sikap positif siswa.Kata kunci: aktivitas siswa, karakter, keterampilan proses sains siswa, media tik tutorial, sikap siswa